Metamorphosis of Productive Zakat: Integrating Zakat Utilization and Women Empowerment for Achieving Sustainable Development Goals - Erlina Kurniawati; Nilna Fauza; Nurlaili Adkhi Rizfa Faiza; Mahamadaree Waeno (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This study explores the metamorphosis of productive zakat through the integration of women empowerment in the Kampung Zakat (Zakat Village) program initiated by BAZNAS in Besole Village, Besuki District, Tulungagung Regency. Employing a qualitative approach based on interviews, observations, and documentation, the study reveals that productive zakat does not merely provide capital assistance, but also initiates a transformation process, economically, socially, and spiritually. Women, especially widows and members of low-income families, became empowered to support their households through small enterprises. More importantly, they were also encouraged to engage in daily giving practices (such as sadaqah subuh), which fostered spiritual growth and nurtures the transition from mustahik (zakat recipient) to muzakki (zakat contributor). This indicateed a metamorphosis from passive dependence to active contribution. The findings affirmed that productive zakat, when combined with structured empowerment and spiritual reinforcement, became an effective tool in realizing SDGs Goals 1 (No Poverty) and 5 (Gender Equality). This study contributes to the field of Islamic philanthropy and zakat management by proposing a contextual, replicable empowerment model that aligns with global development goals while offering practical implications for public policy and localized zakat distribution strategies